ANALISIS RESEPSI KHALAYAK TERHADAP GAYA SEDERHANA JUSUF HAMKA DALAM PODCAST DENNY SUMARGO "KONGLOMERAT TOL ⁉ GW MAU JADI ORANG KAYA BENERAN BUKAN CUMAN TERLIHAT KAYA SAJA ‼" - Muhammad Raihan Naufal Ibrahim (2024)
This study aims to analyze the audience's reception of Jusuf Hamka's simple style in the podcast "Konglomerat Tol ⁉ Gw Mau Jadi Orang Kaya Beneran Bukan Cuman Terlihat Kaya Saja ‼" hosted by Denny Sumargo. The research method uses a qualitative approach with content analysis techniques to explore in-depth understanding of audience responses, perceptions, and interpretations of the content presented. This research is expected to provide deeper insights into how Jusuf Hamka's simple style in the context of podcasts is understood and absorbed by audiences. The findings can make an important contribution to the understanding of public communication, especially in the context of digital media such as podcasts, as well as provide new insights into the aspirations and perceptions of the public towards the theme of financial security presented in the podcast. The author uses a reception analysis method with a qualitative approach, the researcher here uses several research concepts, namely; new media, communication style, reception, audience, simple style. the results of the study indicate that all informants have a uniform view, creating a dominant hegemony in the reception of Jusuf Hamka's simple style. The implications of these findings can be used as a foundation for content creators and media to understand audience preferences and improve the quality of communication in the delivery of simple everyday content.